Taste, Nutrition and Health - Tepper, Beverly J.; Barbarossa, Iole Tomassini (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The sensation of flavor reflects the complex integration of aroma, taste, texture, and chemesthetic (oral and nasal irritation cues) from a food or food component. Flavor is a major determinant of food palatability-the extent to which a food is accepted or rejected-and can profoundly influence diet selection, nutrition, and health. Despite recent progress, gaps in knowledge still remain regarding how taste and flavor cues are detected at the periphery, conveyed by the brainstem to higher cortical levels, and then interpreted as a conscious sensation. Taste signals are also projected to central feeding centers where they can regulate hunger and fullness. Individual differences in sensory perceptions are also well known and can arise from genetic variation, environmental causes, or a variety of metabolic diseases, such as obesity, metabolic syndrome, and cancer. Genetic taste/smell variation could predispose individuals to these same diseases. Recent findings have opened new avenues of inquiry, suggesting that fatty acids and carbohydrates may provide nutrient-specific signals informing the gut and brain of the nature of the ingested nutrients. This Special Issue, Taste, Nutrition, and Health, presents original research communications and comprehensive reviews on topics of broad interest to researchers and educators in sensory science, nutrition, physiology, public health, and health care.